Airbnb 2.0: Is it a sharing economy platform or a lodging corporation?. (June 2020) - Dogru, Tarik; Mody, Makarand; Suess, Courtney; Line, Nathan; Bonn, Mark
Abstract: Research on Airbnb has provided significant evidence that it has an adverse impact on hotel performance. However, the impact of a more recent Airbnb-related phenomenon that remains under-explored is the increasing professionalization of Airbnb and the prevalence of multi-unit hosts who offer more than one listing on the platform and are typically more dynamic in terms of issues like managing inventory and providing more standardized experiences. This professionalization begs the question of whether Airbnb should be considered a sharing economy platform or a lodging corporation (Airbnb 2.0). To answer this question, the present study identifies which types of Airbnb properties (entire homes, private rooms, or shared rooms) and host structures (single- or multi-unit hosts) are the biggest threats to traditional lodging companies in the U.S., and which states are most affected by the presence of Airbnb. The findings have significant implications for researchers and many practitioners associated with the phenomenon. Highlights: Multi-unit hosts and hosts offering entire home listings generate the majority of Airbnb's revenues. Airbnb's market share of supply, demand, and revenues have reached 13.1%, 6.9%, and 10.5%, respectively. Professional host-driven services allowed Airbnb to capture a higher market share in the lodging industry in recent years. Airbnb's growth is spurred by its concentration in 12 states in the U.S., which generate 74% of the company's revenues. State-level supply of Airbnb listings should be considered an important variable in future research.